2020
DOI: 10.28991/scimedj-2020-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Open Metatarsal Fracture in Rats: A Model for Secondary Fracture Healing

Abstract: A fracture model in rats for the study of secondary bone healing was described. Standard open midshaft transverse metatarsal fracture was produced with bone cutting forceps in 28 rats. The commonly open and close fracture models utilized for bone and mineral researches are associated with varying degree of complications ranging from a high degree of fracture comminution to severe associated soft tissue injury which interferes with the healing process. We hypothesized that fracture model in rat third metatarsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Possible limitations regarding the mouse strain and age are already discussed above. As with all mouse models, it should be noted that results may not transfer into pathophysiological processes in humans [ 40 , 41 ]. Mice have a significantly higher metabolism and therefore metabolize drugs more quickly than humans [ 42 ]; thus effects of glucocorticoids might be lesser than expected given that the calculated dose was extrapolated from doses used for therapeutic reasons in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Possible limitations regarding the mouse strain and age are already discussed above. As with all mouse models, it should be noted that results may not transfer into pathophysiological processes in humans [ 40 , 41 ]. Mice have a significantly higher metabolism and therefore metabolize drugs more quickly than humans [ 42 ]; thus effects of glucocorticoids might be lesser than expected given that the calculated dose was extrapolated from doses used for therapeutic reasons in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various genome modification and utilization studies are ongoing. Our SCID rat model may provide a foundation for practical applications of personalized medicine in cancer treatment; it may also be useful in preclinical research regarding bone regeneration, which would benefit from the larger body size in rats (compared to mice) [40][41][42]. In conclusion, our novel SCID rats are expected to be useful in a wide range of applications that extend beyond transplantation studies.…”
Section: Plos Onementioning
confidence: 94%
“…In turn, Qi et al (2014) confirmed that BPA also induces Sertoli cell apoptosis via activating the JNKs/ P38 pathway. In early puberty, BPA disrupts sperm production and changes the spermatogenic tubule epithelial morphology, it can increase Reactive Oxygen Species (ROS) production while decreasing the antioxidant activity of catalase and Superoxide Dismutase (SOD) enzymes (Abubakar et al, 2020;Ullah et al, 2019). There are also studies supporting BPA to induce apoptosis in Sertoli cells by causing excessive ROS production and mitochondrial dysfunction (Wang et al, 2017).…”
Section: Effect Of Bpa On Semen Quality and Male Sexual Functionmentioning
confidence: 99%